RANCANG BANGUN SISTEM INFORMASI INVENTARIS BPJS KETENAGAKERJAAN CABANG PEKALONGAN - Subhiyakto, Egia Rosi; Safina, Nabila (JST (Jurnal Sains dan Teknologi), 2017)
BPJS (Social Security Provider) Employment Branch Pekalongan has the Information Technology division that havingÂ  responsibilities to implement data recapitulation such as Â incoming goods data, outgoing goods data, and inventory data. Currently the data management still uses conventional methods that is manual system resulting some problems, these are; really takes time in searching data and less effective in doing the job. The aim of this study are to design and to build a system inventory information on BPJS Employment Branch Pekalongan supported by waterfall method. In the information system has the features of good data management items of incoming and outgoing goods. Continued to make the reports that can be printed in pdf format. The evaluation was done to measure several parameters such as the usefulness of the application parameters, usability and user satisfaction. Based on the results of the evaluation in the user environment involving four respondents obtained positive results. This indicates that the information system has the benefit value, usefulness and help in improving the performance of the relevant sections.